1996
DOI: 10.1002/eji.1830260604
|View full text |Cite
|
Sign up to set email alerts
|

Death of germinal center B cells without DNA fragmentation

Abstract: During the selection of B cells within germinal centers (GC) on the basis of their affinity for T-dependent antigen, B cells not positively selected are eliminated within GC. This process of B cell death has been considered to be apoptosis. In a recent study, we have reported that, although a substantial number of thymocytes were considered to be dead because of their extremely small cell size and heavy chromatin condensation even though they were not yet phagocytosed (pyknosis), they were devoid of DNA fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…This is comparable to levels reported by Brieva and colleagues (43) and Groot and colleagues (21). Earlier investigations show that DNA degradation and caspase 3 activation generally do not occur until after B cells are engulfed by macrophages (58,59), therefore rendering TUNEL assays and use of fluorometric caspase substrates less reliable for isolating early apoptotic, nonphagocytized GC B cells. Consistent with these reports, our efforts to sort intact GC B cells based on simultaneous staining of AnV and caspase 3 (active form) proved to be problematic (data not presented).…”
Section: Discussionsupporting
confidence: 85%
“…This is comparable to levels reported by Brieva and colleagues (43) and Groot and colleagues (21). Earlier investigations show that DNA degradation and caspase 3 activation generally do not occur until after B cells are engulfed by macrophages (58,59), therefore rendering TUNEL assays and use of fluorometric caspase substrates less reliable for isolating early apoptotic, nonphagocytized GC B cells. Consistent with these reports, our efforts to sort intact GC B cells based on simultaneous staining of AnV and caspase 3 (active form) proved to be problematic (data not presented).…”
Section: Discussionsupporting
confidence: 85%
“…Thymocytes die of neglect by pyknosis. We also demonstrated by the TUNEL method that B lymphocytes in the germinal center die without DNA fragmentation, during the affinity maturation (NAKAMURA et al, 1996). Here we reported that, even in the glucocorticoid treated thymus, most thymocytes die by pyknosis without showing DNA fragmentation, contrary to what has been postulated about the glucocorticoid-induced thymocyte death (WYLLIE, 1980;COHEN and DUKE, 1984;TANUMA and SHIOKAWA, 1994).…”
Section: Discussionmentioning
confidence: 62%
“…10a) (NAKAMURA et al, 1996). By this point, small pyknotic thymocytes probably induced by glucocorticoid treatment were also observed predominantly in the cortex.…”
Section: Ultrastructural Detection Of the Tunel-positive Thymocytes Imentioning
confidence: 68%
See 1 more Smart Citation
“…In contrast to the above-mentioned findings, recent studies on the death of germinal center B cells [14] and glucocorticoid-induced thymocyte death [7] show that the small dead B cells and thymocytes characterized by nuclei with heavy chromatin condensation were ISEL-negative and DNA fragmentation is not primarily involved in the cell death. Therefore, DNA fragmentation detected by ISEL is independent of chromatin condensation.…”
Section: Resultsmentioning
confidence: 74%